Propeller modeling approaches for off–design operative conditions. (15th April 2019) - Gaggero, Stefano; Dubbioso, Giulio; Villa, Diego; Muscari, Roberto; Viviani, Michele
Abstract: In adverse situations, such as maneuvering and motion in waves, severe variations of the propeller inflow may be experienced, resulting in an increase of propeller thrust and torque and in the generation of in-plane loads. This may cause undesired hull-vibratory loads, stress of the propulsive system and even affect somehow the ship dynamic response. Thus, a reliable prediction of these phenomena during design phases is necessary to comply with the increasingly stringent constraints on safety at sea, propulsive efficiency, vibration and noise pollution. In the present work, the capabilities of a propeller solver based on a potential, boundary element method, routinely used in the optimization process of the propulsive device, to analyze the propeller performance under different maneuvering conditions are considered. After a first validation against u R A N S simulations considering a simple oblique flow, the analysis is broadened to a propeller operating in the wake field of a twin screw ship in different maneuvering conditions, for which experimental results from free running tests in model scale are available. The B E M solver is compared also to a steady blade element approach in order to achieve an overview of the respective pros and cons in view of their inclusion in C F D simulations. Highlights: In off-design conditions severe variations of the propeller loads may be experienced. BEM and blade element approaches are used to predict these phenomena. Pure oblique flow and behind ship conditions are considered. The respective pros and cons in view of the inclusion in CFD simulations are analyzed.